2010
DOI: 10.4172/2155-9929.1000056
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ER, PR and Her-2/neu in Endometrial Cancer: A Clinicopathological Study

Abstract: Objective: To determine any association between expression of estrogen receptor (ER), progesterone receptor (PR), and Her-2/neu and clinicopathological features, including survival, of endometrial carcinoma (EMC) patients. Methods: Samples of formalin-fixed, paraffin-embedded tissue of 108 patients with EMC treated at our institution between January 1994 and December 2007 were immunohistochemically studied. Results: ER, PR, and Her-2/neu expression were positive in 59.3%, 65.7% and 2.8% of cases, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Thus, type II is not completely estrogen-independent (5). Previous studies supported the role of ERα in the development of EC (4, 6). Additionally, G-protein-coupled receptor-30 (GPR30), which encodes a multi-pass membrane protein mediating the estrogen action of intracellular estrogen receptor (7, 8), has been suggested to be an indicator of EC progression (9).…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Thus, type II is not completely estrogen-independent (5). Previous studies supported the role of ERα in the development of EC (4, 6). Additionally, G-protein-coupled receptor-30 (GPR30), which encodes a multi-pass membrane protein mediating the estrogen action of intracellular estrogen receptor (7, 8), has been suggested to be an indicator of EC progression (9).…”
Section: Introductionmentioning
confidence: 54%
“…In China, EC was diagnosed in 63,400 patients and accounted for more than 21,800 deaths in 2016 (3). EC has been proposed to be classified into two pathogenetic groups, of which type I mostly occurs in pre- and peri-menopausal women with a history of unopposed estrogen exposure (4). However, studies found no difference in the positivity of estrogen receptor (ER) or progesterone receptor (PR) as well as the level of sex hormones between these two types of EC.…”
Section: Introductionmentioning
confidence: 99%